Digital Dissemination of Waste Management Smart Building as a Sustainable Solution for Waste Management: Sosialisasi Digital Gagasan Waste Management Smart Building sebagai Solusi Pengelolaan Limbah Berkelanjutan - Priyambodo; Lestari, Indah Ayu; Damayanti, Lisa Alfina; Azzami, Fahrul; Muttaqin, Faiz Zainul; Ahsan, Fathan Naufal; Oktiani, Hestin (Yayasan Ahmar Cendekia Indonesia, 2023)
Waste management in Indonesia is one of the problems that cannot be handled optimally. Waste Management Smart Building (WMSB) is an integrated waste management idea, both in the form of plastic waste and agricultural waste based on a zero waste system. Digital dissemination carried out through Unila TV as an effort to overcome integrated waste management. The stages of implementation carried out include; pre-production, production and post-production. The achievement indicator is seen from the percentage of likes and the percentage of positive comments from viewers. Data analysis is presented in graphical form and analyzed descriptively. Based on the analysis obtained from the video that broadcasted on Unila TV starting June 22, 2023, it has currently been watched 398 times (19.8%). There were 134 viewers who gave reactions in the form of likes (33.66%) and no viewers who gave dislike reactions (0%). Based on the comments given by the audience, 100% are positive which is expected to be a cognitive response that arises after an understanding regarding the information conveyed through the video.